2020
DOI: 10.1590/0004-282x20190156
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ventilatory function in patients with spinocerebellar ataxia type 2

Abstract: Subclinical ventilatory dysfunction is observed in individuals with spinocerebellar ataxias (SCA). No studies have correlated ventilatory dysfunction to clinical and functional decline in SCA2. Objective: To evaluate the relationship between the values of peak expiratory flow (PEF), maximum inspiratory pressure (MIP), and presence of respiratory complaints with age, disease duration, age at onset of symptoms, balance scores, independence in basic (ADL) and instrumental (IADL) Activities of Daily Living (ADLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The pulmonary dysfunction in SCA is due to a lack of muscle coordination and inability to sustain respiratory effort 43 . A recent study with SCA2 patients suggested that ventilatory dysfunction, even asymptomatic, is related to increased imbalance, functional dependence, and worse SARA score 44 . Ventilatory support, assisted cough, and air-stacking technique should be prescribed to these patients as needed to relieve their symptoms.…”
Section: Respiratory Rehabilitationmentioning
confidence: 99%
“…The pulmonary dysfunction in SCA is due to a lack of muscle coordination and inability to sustain respiratory effort 43 . A recent study with SCA2 patients suggested that ventilatory dysfunction, even asymptomatic, is related to increased imbalance, functional dependence, and worse SARA score 44 . Ventilatory support, assisted cough, and air-stacking technique should be prescribed to these patients as needed to relieve their symptoms.…”
Section: Respiratory Rehabilitationmentioning
confidence: 99%